Design of Weather Monitoring Sensors and Soil Humidity in Agriculture Using Internet of Things (IoT) - Utama, Yoga Alif Kurnia; Widianto, Yonatan; Hari, Yulius; Habiburrahman, Muhammad (Transactions on Engineering and Computing Sciences, 2019)
One of the developments in internet technology at the moment is the Internet of things (IoT). IoT is a concept that aims to expand the benefits of internet connectivity that is connected continuously and can monitor a system or object. As for capabilities such as data sharing, remote control, including monitoring a system. Because Indonesia is an agricultural country, this study tries to make a monitoring of a smart farmer system that helps people monitor plants on their farms. This system will monitor weather parameters such as temperature and humidity conditions, as well as soil moisture conditions. If soil moisture is reduced due to heat, then water will automatically be pumped and flow to the plant. Farm owners can also monitor the condition of their plants in real time remotely through the Blynk application media, Facebook website, and Twitter. Based on the test results, the system can measure the environmental conditions of plants, can connect to the internet and be able to send data from sensor measurements to the Blynk application, Facebook website and Twitter. With the development of these systems and devices, it is hoped that the farmers or the community can monitor the environmental conditions of the plants